2013
DOI: 10.1371/journal.pone.0055196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Oncologic Outcome of Colorectal Cancer Patients: Colon vs. Rectal Cancer

Abstract: BackgroundTo evaluate the impact of diabetes on outcomes in colorectal cancer patients and to examine whether this association varies by the location of tumor (colon vs. rectum).Patients and methodsThis study includes 4,131 stage I-III colorectal cancer patients, treated between 1995 and 2007 (12.5% diabetic, 53% colon, 47% rectal) in South Korea. Cox proportional hazards modeling was used to determine the prognostic influence of DM on survival endpoints.ResultsColorectal cancer patients with DM had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 47 publications
3
58
0
2
Order By: Relevance
“…Previous studies have suggested that a diagnosis of DM has a negative impact on cancer outcomes [76, 77]; therefore, inclusion of non-DM patients in comparator groups could underestimate the beneficial effect of metformin. Owing to insufficient study numbers, it was only possible to analyse the effect of the presence or absence of non-DM patients in the comparator group for RFS in prostate cancer, where no evidence for an effect was found.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that a diagnosis of DM has a negative impact on cancer outcomes [76, 77]; therefore, inclusion of non-DM patients in comparator groups could underestimate the beneficial effect of metformin. Owing to insufficient study numbers, it was only possible to analyse the effect of the presence or absence of non-DM patients in the comparator group for RFS in prostate cancer, where no evidence for an effect was found.…”
Section: Discussionmentioning
confidence: 99%
“…For example, type 2 diabetes has been reported to have a direct negative effect on tumor recurrence and survival in patients with colon cancer (60). In general, survival for cancer patients with type 2 diabetes is worse than for their nondiabetic counterparts because of indirect factors associated with diabetes.…”
Section: Type 2 Diabetes Mellitus and Cancermentioning
confidence: 99%
“…Although bias might explain some of the associations, such as detection bias for bladder cancer (9) or reverse causality for pancreatic cancer, several large meta-analyses support the reproducibility of these observations (10,11). Additional studies showed higher mortality from colorectal (12,13), and breast cancers (14) among patients with diabetes, however the results were inconclusive and might not reflect cancer-specific mortality but rather mortality secondary to comorbidities associated with the metabolic syndrome (i.e. coronary artery disease), administration of less aggressive cancer treatment or difference in response to therapy in patients with diabetes (14-18).…”
Section: Introductionmentioning
confidence: 99%